Organizational chart that redistributes the physical - recreational activities of the adult in the community context - Damaris Lacera-Terry (Universidad de Guantánamo, 2013)
The research work addresses the shortcomings that exist with content distribution and recreational physical care of the elderly that adversely affect the exercise without allowing the realization of this important community activity, and proposed to develop an organization that redistributes physical activities - elderly recreational significantly and community context specific Angel Mendol, which responds to the line that is on studies of changes in social behavior in the community. After set-contextual theoretical framework was achieved draw up an organization giving solution addressed the issue.